2017
DOI: 10.3892/etm.2017.4802
|View full text |Cite
|
Sign up to set email alerts
|

Preventive effects of Polygonum multiflorum on glucocorticoid-induced osteoporosis in rats

Abstract: In Traditional Chinese Medicine, Polygonum multiflorum (PM) is known for its anti-aging properties. A previous study by our group showed that extracts of PM were able to prevent and treat bone loss in vivo, and the active components emodin and 2,3,5,4,-tetrahydroxystilbene-2-O-β-glucoside (TSG) promoted the osteogenic differentiation of mesenchymal stem cells in vitro. The aim of the present study was to investigate the preventive effects of PM on glucocorticoid-induced osteoporosis (GIO) in rats. A crude extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 31 publications
(31 reference statements)
0
6
0
Order By: Relevance
“…TSG treatments did not produce significant influence on fasting blood glucose level of diabetic mice; therefore, the therapeutic effects resulting from the drug treatment was unlikely to be mediated through targeting the pancreas or by reducing hyperglycemia. In addition, the present study indicated that TSG might be an important bone health factor contained in P. multiflorum Thunb, which was reported to exert preventive effects on glucocorticoid‐ and ovariectomy‐induced osteoporosis (Hwang et al, ; Zhou et al, ).…”
Section: Discussionmentioning
confidence: 55%
“…TSG treatments did not produce significant influence on fasting blood glucose level of diabetic mice; therefore, the therapeutic effects resulting from the drug treatment was unlikely to be mediated through targeting the pancreas or by reducing hyperglycemia. In addition, the present study indicated that TSG might be an important bone health factor contained in P. multiflorum Thunb, which was reported to exert preventive effects on glucocorticoid‐ and ovariectomy‐induced osteoporosis (Hwang et al, ; Zhou et al, ).…”
Section: Discussionmentioning
confidence: 55%
“…[41] It is also reported to boost immune function and increase sexual vigor; [42] be a blood toner, improve cellular energetics, and fortify muscles, tendons, and bones. [43] P. multiflorum significantly inhibited LPS-iNOS and COX-2 protein and mRNA expression, as well as inhibited nitric oxide and prostaglandin E2 production. LPS-induced NF-κB transactivation and nuclear translocation were significantly inhibited.…”
Section: Water-extract Of Polygonum Multiflorum (Family Asparagaceae) Commonly Known As Fo-ti Root Extractmentioning
confidence: 88%
“…Gender and strain-specific efficacy of GCs have been previously demonstrated [ 92 , 93 ]. The effects of prednisone (6 mg/kg/day P.O) in male and female Sprague Dawley rats were investigated on bone parameters for 21 weeks [ 37 ]. Findings demonstrated that the BV/TV parameter decreased by 52% and 27.0% at the femur and L4 vertebra, respectively, in females, whereas in males, the loss was 28.6% and 14.0% at the femur and L4, respectively.…”
Section: Discussionmentioning
confidence: 99%